2000
DOI: 10.1161/01.cir.101.19.2247
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Adhesion Molecules in Humans

Abstract: Background-We assessed the role of glucose and insulin in the regulation of circulating levels of soluble intercellular adhesion molecule-1 (sICAM-1) and vascular adhesion molecule-1 (sVCAM-1) in normal subjects and in patients with type 2 diabetes. Methods and Results-Plasma glucose concentrations were acutely raised in 10 normal subjects and 10 newly diagnosed, complication-free type 2 diabetic patients and maintained at 15 mmol/L for 2 hours. In normal subjects, plasma sICAM-1, but not sVCAM-1, levels rose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
54
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 197 publications
(61 citation statements)
references
References 25 publications
7
54
0
Order By: Relevance
“…We observed a slight, but significant, reduction in soluble ICAM-1 levels when chronic hyperglycemia was reduced by CSII. This is in agreement with a recent study by Marfella et al in patients with Type 2 diabetes, where increased levels of sICAM-1, induced by acute hyperglycemia, were restored when hyperglycemia was corrected with insulin or L-arginine supplementation [32]. Also, elevated levels of TNFa have been demonstrated in patients with Type 1 diabetes during impaired control [34] and elevated levels may induce the expression of ICAM-1.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We observed a slight, but significant, reduction in soluble ICAM-1 levels when chronic hyperglycemia was reduced by CSII. This is in agreement with a recent study by Marfella et al in patients with Type 2 diabetes, where increased levels of sICAM-1, induced by acute hyperglycemia, were restored when hyperglycemia was corrected with insulin or L-arginine supplementation [32]. Also, elevated levels of TNFa have been demonstrated in patients with Type 1 diabetes during impaired control [34] and elevated levels may induce the expression of ICAM-1.…”
Section: Discussionsupporting
confidence: 92%
“…Hyperglycemia increases the expression of ICAM-1 on endothelial cells [30], and soluble plasma levels of ICAM-1 are increased in patients with Type 1 diabetes [31] and during acute hyperglycemia [32,33]. We observed a slight, but significant, reduction in soluble ICAM-1 levels when chronic hyperglycemia was reduced by CSII.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…More recently it has been reported that specifically controlling post-prandial hyperglycaemia using a rapid-acting secretagogue (repaglinide) compared with glyburide resulted in a similar improvement of HbA 1c but was associated with a regression of carotid artery atherosclerosis [28]. In addition to these data, other clinical and experimental studies suggest that post-challenge hyperglycaemia or acute elevation of plasma glucose is deleterious for diverse functions related to atherogenesis [29][30][31][32][33][34][35][36][37][38][39]. Thus, the bulk of epidemiological, clinical and experimental evidence strongly suggests that efforts to monitor and control the common phenomenon of post-prandial hyperglycaemia should have uniquely beneficial effects on the chronic complications of type 2 diabetes.…”
Section: Discussionmentioning
confidence: 97%
“…57 Elevations in plasma glucose levels also are associated with ICAM-1 level increases that decline in response to insulin treatment. 58,59 Hypercholesterolemia produces lesions with a higher lipid content. 51,60 Induction of monocyte chemotactic protein (MCP-1) by oxidized low-density lipoprotein (LDL) cholesterol may assist monocyte diapedesis through the endothelium and into the intima.…”
Section: Risk Factors and Possible Pathogenic Mechanismsmentioning
confidence: 99%